2017
DOI: 10.1097/md.0000000000007426
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant transarterial chemoembolization after radical resection contributed to the outcomes of hepatocellular carcinoma patients with high-risk factors

Abstract: We aim to investigate the effects of postoperative adjuvant transarterial chemoembolization (TACE) on survival and recurrence in hepatocellular carcinoma (HCC) patients after radical resection. A total of 320 HCC patients underwent radical resection between January 2010 and January 2014 in Qilu Hospital, Shandong University were divided into 4 groups according to the frequency of postoperative adjuvant TACE. Patients were further stratified into subgroups (tumor diameter ≤5 or >5 cm) with low or high risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
(28 reference statements)
1
12
0
Order By: Relevance
“…It is encouraging that our results added that postoperative adjuvant TACE was associated with higher RFS and OS in patients with tumor size ≤5 cm accompanied by mVI. These data are in agreement with previous studies, which also showed that adjuvant TACE significantly improved postoperative prognosis in patients with multiple tumors , poor differentiation , or portal vein tumor thrombus . Generally, many HCC recurrences are likely to be related to minimal residual tumors that may not have been detected before or during surgery and micro metastases that may have been shed from tumor masses removed during operation.…”
Section: Discussionsupporting
confidence: 92%
“…It is encouraging that our results added that postoperative adjuvant TACE was associated with higher RFS and OS in patients with tumor size ≤5 cm accompanied by mVI. These data are in agreement with previous studies, which also showed that adjuvant TACE significantly improved postoperative prognosis in patients with multiple tumors , poor differentiation , or portal vein tumor thrombus . Generally, many HCC recurrences are likely to be related to minimal residual tumors that may not have been detected before or during surgery and micro metastases that may have been shed from tumor masses removed during operation.…”
Section: Discussionsupporting
confidence: 92%
“…Meta-analysis of RCTs of adjuvant interferon after resection showed a positive effect, but almost all published studies have been conducted in Asian patients and this could not be confirmed in Western cohorts [ 61 ]. In HCCs with vascular invasion or other high-risk factors such as poor differentiation and tumour diameter >5 cm, adjuvant transcatheter arterial chemoembolization (TACE) may provide better control of recurrence risk, especially with multiple treatment sessions [ 64 , 65 ].…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…It was shown that adjuvant TACE (2 or 3 times) after radical surgical resection was beneficial for patients with HCC, even in the presence of poor differentiation and microvascular invasion, especially for those patients with a tumor diameter of >5 cm. Hence, within the context of the current study, in which only a single session of TACE was performed in patients with a lower degree of disease, this aspect needs to be mentioned, instead of concluding that THM was better . Zhai et al demonstrated that the 5‐year recurrence‐free survival (RFS) rates were clearly better in the TACE group (69.57% vs 54.44%), but the median RFS was reported to be higher in the THM group (85.8 months vs 26 months) with incomplete documentation of confidence intervals.…”
mentioning
confidence: 85%
“…Hence, within the context of the current study, in which only a single session of TACE was performed in patients with a lower degree of disease, this aspect needs to be mentioned, instead of concluding that THM was better. 6 Zhai et al demonstrated that the 5-year recurrence-free survival (RFS) rates were clearly better in the TACE group (69.57% vs 54.44%), but the median RFS was reported to be higher in the THM group (85.8 months vs 26 months) with incomplete documentation of confidence intervals. This could have happened because the authors excluded missing data (called as complete case analysis) and wasted useful information because other observed variables associated with the missing variables also were excluded.…”
mentioning
confidence: 99%